Vascular risk factors and amyloid pathology: Additive or interactive associations?: Vascular factors of Alzheimer's disease. (7th December 2020) - Schott, Jonathan M; Lane, Christopher A; Barnes, Jo; Keuss, Sarah E; James, Sarah‐Naomi; Lu, Kirsty; Sudre, Carole H; Cash, David M; Parker, Thomas D; Malone, Ian B; Keshavan, Ashvini; Murray‐Smith, Heidi; et al.
Abstract: Background: The two commonest contributors to late‐life cognitive impairment are Alzheimer's (AD) and cerebrovascular disease; these two conditions almost invariably overlap. Understanding the determinants of the pathologies that underpin these conditions and how they interact to influence late‐life brain health is vital for rational risk prevention and for clinical trials. Method: Data from the Insight 46 cohort will be presented, comprising individuals from the MRC 1946 British Birth Cohort all born in mainland Britain in one week in 1946. These individuals have been followed prospectively including serial measures of cognition from age 8, cardiovascular risk since the mid‐30s, and a range of cardiac and vascular outcomes in their 60s. At age 69‐71 they had detailed cognitive testing, 3T‐MRI including determination of white matter hyperintensity volume (WMHV) and 18 F‐Florbetapir (β‐amyloid) PET. All individuals are being seen for a second visit, two‐years after the first. Results: A total of 502 participants were assessed cross‐sectionally; data from up to 465 participants (51.0% male, mean age=70.7±0.7, 18.2% β‐amyloid positive) are available. Results of cross‐sectional analyses investigating the relationships between life course cardiovascular risk factors genetics, β‐amyloid and WMHV will be presented, alongside analyses of the associations of these pathologies with cross‐sectional cognitive function and MRI metrics. Investigations exploring mechanistic relationships e.g. between cardiac and vascular outcomes including pulse wave velocity and echocardiography, β‐amyloid and WMHV and cognition will be presented. Interim results of analyses exploring relationships between baseline β‐amyloid and WMHV and rates of cognitive decline and brain atrophy will be described in n=250 (47.6% female, age=72.5±0.33, 18.1% β‐amyloid positive) of the cohort. These results will be compared and contrasted with those from other cohort studies including the Atherosclerosis Risk in Communities (ARIC) study, and Mayo Clinic Study of Ageing. Conclusion: Combining life course data, contemporaneous measurement of PET‐amyloid status, WMHV and cognition, vascular metrics and longitudinal measures of brain atrophy and cognitive change provides a powerful opportunity to explore how and when vascular and β‐amyloid pathology influence brain health in later‐life. Emerging evidence from several studies suggest that vascular risk influences the development of cognitive impairment and dementia principally via non‐amyloidogenic pathways.